Examining the negative perception on the use of Ghanaian Language as a medium of instruction in Basic schools in Ghana - Nyantakyi, Gabriel Kwasi; Armoo , Anthony Kwaw; Poku, Felicia Asamoah –; Adobea, Agnes (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
This investigation examined the negative perception surrounding the use of Ghanaian languages as a medium of instruction in basic schools across Ghana. The medium of instruction in Ghanaian basic schools has predominantly been English, inherited from the colonial era, with minimal integration of local languages. However, recent educational reforms have called for the incorporation of Ghanaian languages into the curriculum to enhance learning outcomes and promote cultural identity. The investigation adopts an exploratory approach, utilizing qualitative methods to gather data from teachers, parents, and students in selected basic schools across Ghana. The regions considered in this investigation were: Bono, Ashanti and Central. Semi-structured interviews and focus group discussions were conducted to explore stakeholders’ perceptions and experiences regarding the use of Ghanaian languages as a medium of instruction. In all, one hundred (100) participants were used as population sampling in line with purpose of the investigation. It was revealed that, negative perceptions towards using Ghanaian languages as a medium of instruction in basic schools exist among various stakeholders. Some of the identified concerns include limited career opportunities for students, reduced competence in English, potential exclusion from global educational platforms, and a perceived lack of standardization and resources for Ghanaian language instruction. The study recommends a balanced approach that recognizes the importance of English as a global language while promoting the use of Ghanaian languages as a supportive medium of instruction. Vygotsky (1978) sociocultural theory underpinned this investigation. This theory emphasized the importance of social interactions, cultural tools (such as language, symbols, and artifacts), and the role of more knowledgeable individuals in supporting a learner’s development. The theory proposes that cognitive development occurs through collaboration, guidance, and the internalization of cultural practices and concepts.